2020
DOI: 10.1002/ajmg.b.32827
|View full text |Cite
|
Sign up to set email alerts
|

Genetic overlap and causality between substance use disorder and attention‐deficit and hyperactivity disorder

Abstract: Substance use disorder (SUD) often co-occur at high prevalence with other psychiatric conditions. Among them, attention-deficit and hyperactivity disorder (ADHD) is present in almost one out of every four subjects with SUD and is associated with higher severity, more frequent polysubstance dependence and increased risk for other mental health problems in SUD patients. Despite studies suggesting a genetic basis in the co-occurrence of these two conditions, the genetic factors involved in the joint development o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
36
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 60 publications
0
36
0
Order By: Relevance
“…In terms of health characteristics, previous studies have reported a higher risk of substance use and dependence, for example, consumption of alcohol and smoking, in patients with ADHD [32,33]. In addition, a possible genetic basis for the co-occurrence of substance use disorder and ADHD has been reported [34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of health characteristics, previous studies have reported a higher risk of substance use and dependence, for example, consumption of alcohol and smoking, in patients with ADHD [32,33]. In addition, a possible genetic basis for the co-occurrence of substance use disorder and ADHD has been reported [34].…”
Section: Discussionmentioning
confidence: 99%
“…In terms of health characteristics, previous studies have reported a higher risk of substance use and dependence, for example, consumption of alcohol and smoking, in patients with ADHD [ 32 , 33 ]. In addition, a possible genetic basis for the co-occurrence of substance use disorder and ADHD has been reported [ 34 ]. Our study findings supported this, though fewer ASRS+ respondents reported currently drinking alcohol, alcoholism occurred at an approximately 4-36-fold greater rate among ASRS-positive respondents compared to ASRS-negative respondents.…”
Section: Discussionmentioning
confidence: 99%
“…Genome‐wide association studies (GWAS) have shown shared genetic liability between ADHD and substance use 6,7 . Recent Mendelian randomization studies have also revealed a causal pathway from liability for ADHD to tobacco and cannabis use, but evidence for causal effects on SUD is not conclusive 8–12 . ADHD and SUD patients also show many similarities at (endo)phenotypic level.…”
Section: Introductionmentioning
confidence: 99%
“…This special issue includes a total of seven works (Cabrera-Mendoza et al, 2021;Gerring, Vargas, Gamazon, & Derks, 2020;Lai et al, 2020;Maldonado et al, 2021;Markunas et al, 2020;Soundararajan et al, 2021;Vilar-Rib o et al, 2020) that cover different topics on the genomics and epigenomics of SUD, one of them a review and the rest original research articles.…”
mentioning
confidence: 99%
“…Vilar‐Ribó et al (2020) address the important topic of genetic overlap in psychiatric disorders. They use different tools to explore the shared genetics between SUD and attention‐deficit hyperactivity disorder (ADHD), two conditions that are frequently comorbid.…”
mentioning
confidence: 99%